In Situ Trans-Esterification of Residual Oils in Spent Bleaching Clays from Vegetable Oil Refineries - Phakahan, Prapassorn; Aryusuk, Kornkanok; Lilitchan, Supathra; Krisnangkura, Kanit (Journal of Technology Innovations in Renewable Energy, 2016)
Spent bleaching clays (SBCs) from vegetable oil refineries are industrial wastes. The clays contain large amount of oils (20-25%), which are good feedstock for biodiesels. Non-thermal in situ trans-methylation and trans-ethylation of oils in the SBC from rice bran oil (RBO), crude palm oil (CPO) and palm kernel oil (PKO) are rapid and can be accomplished in minutes with an alkaline catalyst. Thus, the process may possibly be used for large scale preparation of ethyl biodiesel.